Interaksi Edukatif dan Pengelolaan Kelas yang Efektif dalam Pembelajaran Bahasa Arab - Irsad, Ridho Muamar; Sutarni, Zakiyyah Ambarwati; Putri, Nurul Cintia (Kalimatuna: Journal of Arabic Research, 2024)
Arabic language learning in educational institutions faces various challenges. Effective interactions between teachers and students, and among students, are crucial for success. These interactions enhance motivation, interest, and engagement. Effective classroom management is essential for a conducive learning environment. This study, using a descriptive-analytical and qualitative approach, reviews literature, prior research, and teaching observations. Findings show interactive methods, like group discussions and presentations, boost participation and language mastery. Structured interactions and clear, consistent classroom rules support learning outcomes. The study highlights how educational interactions and management together improve student motivation and performance, with technology enhancing engagement and classroom control. Both elements are vital for effective Arabic language learning.